A constraint programming approach to the additional relay placement problem in wireless sensor networks - Quesada, Luis; Sitanayah, Lanny; Brown, Kenneth N.; O’Sullivan, Barry; Sreenan, Cormac J. (Constraints : an international journal, 2015)
A Wireless Sensor Network (WSN) is composed of many sensor nodes which transmit their data wirelessly over a multi-hop network to data sinks. Since WSNs are subject to node failures, the network topology should be robust, so that when a failure does occur, data delivery can continue from all surviving nodes. A WSN is k -robust if an alternate length-constrained route to a sink is available for each surviving node after the failure of up to k -1 nodes. A WSN is strongly k -robust if there are k disjoint length-constrained routes to a sink for each node. Determining whether a network is k -robust is polynomial. However, determining whether a network is strongly k -robust is an NP-complete problem. We develop a Constraint Programming (CP) approach for deciding strongly k-robustness that outperforms a Mixed-Integer Programming (MIP) model on larger problems. A network can be made (strongly) robust by deploying extra relay nodes. We extend our CP approach to an optimisation approach by using QuickXplain to search for a minimal set of relays, and compare it to a state-of-the-art local search approach.